Prodrug of ICRF-193 provides promising protective effects against chronic anthracycline cardiotoxicity in a rabbit model in vivo - Kollárová-Brázdová, Petra; Lenčová-Popelová, Olga; Karabanovich, Galina; Kocúrová-Lengvarská, Júlia; Kubeš, Jan; Váňová, Nela; Mazurová, Yvona; Adamcová, Michaela; Jirkovská, Anna; Holečková, Magdalena; Šimůnek, Tomáš; Štěrbová-Kovaříková, Petra; et al. (Clinical science (London, England, 2021)
The anthracycline (ANT) anticancer drugs such as doxorubicin or daunorubicin (DAU) can cause serious myocardial injury and chronic cardiac dysfunction in cancer survivors. A bisdioxopiperazine agent dexrazoxane (DEX) has been developed as a cardioprotective drug to prevent these adverse events, but it is uncertain whether it is the best representative of the class. The present study used a rabbit model of chronic ANT cardiotoxicity to examine another bisdioxopiperazine compound called GK-667 (meso-(butane-2,3-diylbis(2,6-dioxopiperazine-4,1-diyl))bis(methylene)-bis(2-aminoacetate) hydrochloride), a water-soluble prodrug of ICRF-193 (meso-4,4'-(butan-2,3-diyl)bis(piperazine-2,6-dione)), as a potential cardioprotectant. The cardiotoxicity was induced by DAU (3 mg/kg, intravenously, weekly, 10 weeks), and GK-667 (1 or 5 mg/kg, intravenously) was administered before each DAU dose. The treatment with GK-667 was well tolerated and provided full protection against DAU-induced mortality and left ventricular (LV) dysfunction (determined by echocardiography and LV catheterization). Markers of cardiac damage/dysfunction revealed minor cardiac damage in the group co-treated with GK-667 in the lower dose, whereas almost full protection was achieved with the higher dose. This was associated with similar prevention of DAU-induced dysregulation of redox and calcium homeostasis proteins. GK-667 dose-dependently prevented tumor suppressor p53 (p53)-mediated DNA damage response in the LV myocardium not only in the chronic experiment but also after single DAU administration. These effects appear essential for cardioprotection, presumably because of the topoisomerase IIβ (TOP2B) inhibition provided by its active metabolite ICRF-193. In addition, GK-667 administration did not alter the plasma pharmacokinetics of DAU and its main metabolite daunorubicinol (DAUol) in rabbits in vivo. Hence, GK-667 merits further investigation as a promising drug candidate for cardioprotection against chronic ANT cardiotoxicity.
Keywords: kardiomyocyty; Diketopiperazines; Male; Myocytes, Cardiac; Ventricular Function, Left; poškození DNA; Tumor Suppressor Protein p53; Rabbits; Animals; Cardiotoxicity; funkce levé komory srdeční; prekurzory léčiv; daunomycin; kardiotoxicita; inhibitory topoisomerasy II; Humans; chronická nemoc; DNA Damage; HL-60 buňky; anthracycline cardiotoxicity; mužské pohlaví; remodelace komor; Ventricular Remodeling; Daunorubicin; modely nemocí na zvířatech; Cardiomyopathies; fibróza; dexrazoxane; cardioprotection; zvířata; Chronic Disease; Prodrugs; Ventricular Dysfunction, Left; kardiomyopatie; ICRF-193; Fibrosis; bisdioxopiperazine; HL-60 Cells; diketopiperaziny; lidé; dysfunkce levé srdeční komory; Topoisomerase II Inhibitors; topoisomerase IIbeta; Disease Models, Animal; nádorový supresorový protein p53; králíci